Exploring the Impact of Fear of Missing Out (FOMO) on Generation Z's Luxury Purchasing Intentions : Analysis of Critical Design Elements Triggering FOMO - Havlová, Štěpánka (2024)
This thesis investigates the impact of Fear of Missing Out (FOMO) on Generation Z's purchasing intentions within the luxury market, focusing on the design elements in social media marketing that effectively trigger FOMO. With Generation Z projected to become a dominant consumer segment in the luxury market, understanding the psychological triggers that influence their purchasing behaviour is critical for marketers. Despite the growing interest in FOMO within consumer psychology, there is a notable gap in research regarding how FOMO specifically influences the decision-making process for tangible luxury goods, as opposed to more transient experiences. This study addresses this gap by formulating and testing hypotheses related to the effectiveness of textual and visual FOMO-triggering elements in luxury advertisements. Through a controlled experimental design involving 82 participants aged 18 to 27, the research employed a 4x1 between-subjects design to evaluate the impact of different FOMO appeals on both state-FOMO and intention to purchase. The study revealed that while FOMO-triggering appeals can significantly alter both emotional states and purchasing intentions, the effect is not uniformly positive. In some cases, these appeals reduced the intention to purchase, particularly when they reduced the perception of luxury. The findings are significant for luxury marketers as they demonstrate that the use of FOMO in marketing must be carefully tailored to avoid unintended consequences, such as diminished purchase intentions. This research contributes to the field by providing a nuanced understanding of how FOMO can be effectively integrated into luxury branding strategies, emphasizing the importance of aligning FOMO appeals with the psychological profiles of Generation Z consumers and the nature of the product marketed to maintain brand prestige and drive sales.